Correction of mutations within the cystic fibrosis transmembrane conductance regulator by site-directed RNA editing - Montiel-Gonzalez, Maria Fernanda (National Academy of Sciences, 2013)
Adenosine deaminases that act on RNA are a conserved family of enzymes that catalyze a natural process of site-directed mutagenesis. Biochemically, they convert adenosine to inosine, a nucleotide that is read as guanosine during translation; thus when editing occurs in mRNAs, codons can be recoded and the changes can alter protein function. By removing the endogenous targeting domains from human adenosine deaminase that acts on RNA 2 and replacing them with an antisense RNA oligonucleotide, we have engineered a recombinant enzyme that can be directed to edit anywhere along the RNA registry. Here we demonstrate that this enzyme can efficiently and selectively edit a single adenosine. As proof of principle in vitro, we correct a premature termination codon in mRNAs encoding the cystic fibrosis transmembrane conductance regulator anion channel. In Xenopus oocytes, we show that a genetically encoded version of our editase can correct cystic fibrosis transmembrane conductance regulator mRNA, restore full-length protein, and reestablish functional chloride currents across the plasma membrane. Finally, in a human cell line, we show that a genetically encoded version of our editase and guide RNA can correct a nonfunctional version of enhanced green fluorescent protein, which contains a premature termination codon. This technology should spearhead powerful approaches to correcting a wide variety of genetic mutations and fine-tuning protein function through targeted nucleotide deamination.